The extent of sustainable extension support to beneficiaries in the Proactive Land Acquisition Strategy Nkangala District Mpumalanga South Africa - Terblanche, S.E. (Stephanus Esaias), 1940- (University of Pretoria, 2017)
Dissertation (MSc (Agric))--University of Pretoria, 2017.